Do you know what FRIDs are? / Mohd Shah Rezan Hamzah and Mahmathi Karuppanan - Hamzah, Mohd Shah Rezan; Karuppanan, Mahmathi (Faculty of Pharmacy, 2024)
Falls present a noteworthy public health issue due to their association with many complications, including fall-related injuries, psychological and social consequences, increased healthcare costs, and mortality. In the United States (U.S.), it was reported that more than one out of four older people aged 65 and older fell annually [1]. According to the Centers for Disease Control and Prevention (CDC), death rates following falls for older people in the U.S. increased by 30% from 2007 to 2016, and were expected to rise by 2030, with the anticipation of seven fall deaths every hour. Falls among older people are a common source of high injury severity, such as broken bones and head injuries and mortality [2]. Falls are also the most common cause of traumatic brain injury in the U.S., which may result in death [3]. According to the CDC, 3 million older people are treated in emergency departments each year for fall injuries, and nearly 1 million older people are hospitalized each year for head injuries and hip fractures due to falls. This situation has resulted in the U.S. spending more than USD 50 billion on total medical costs associated with falls [4].